Stock-Market Equilibrium and the Dividend Yield - Kramer, Charles (IMF Working Papers; Working Paper ;, 1996)
Can fundamentals account for the recent performance of the U.S. stock market? The price/earnings ratio is out of line with historical averages, and the dividend/price ratio has recently reached a historic low. These developments and record levels of inflows into mutual funds have led some to conclude that stock prices are above their fundamental levels. This paper assesses the recent rise in the stock market using a model for the equilibrium dividend/price ratio. While economic variables can account for most of the recent fall in the dividend/price ratio, mutual-fund inflows still have some marginal explanatory power.